KOMPARASI STRATEGI INVESTASI DENGAN PENDEKATAN MOVING AVERAGE CONVERGENCE DIVERGENCE (MACD), RELATIVE STRENGTH INDEX (RSI), DAN BUY AND HOLD - Setiani, Okki Arnelia; Nugroho, Dian Ari (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
The objective of this research is to identify returns generated from investment strategies that use Moving Average Convergence Divergence (MACD), Relative Strength Index (RSI), and Buy and Hold approaches applied by companies consistently listed on the LQ45 Index during the 2015-2020 period. The identification of the return can help determine strategies with the most optimal return along with the stocks. The sample was selected using purposive sampling with the criteria of companies whose stocks have never been suspended, were actively traded during the research period, and were consistently included in LQ45 Index. The results of the observations on the 26 sample companies have led to following findings. First, returns gained from MACD, RSI, and Buy and Hold are different. Second, Buy and Hold gives most optimal return average. Third, stocks with the most optimum return are BBCA, i.e. 79.16%. The return was gained through Buy and Hold strategy, a strategy that does not require many transactions.